Teaching strategies for nurse educators - DeYoung, Sandra; Rowlang, Beatrice L. (Singapore : Pearson, 2003)
This book is designed to help nurses learn how t oteach. Whether they are teaching patients, staf, or students in an academic setting, nurses who are in the educator role need a theory base from which to work.
Part I: Teaching and learning -- Part II: The learner -- Part III:teaching strategies
Includes index.
Keywords: NURSING -- STUDY AND TEACHING